The Impact of Government Spending Policy on the Human Development in the Context of Overcoming the “Middle Income Trap” - E. Sandoyan; A. Margaryan (Финансы: теория и практика, 2024)
The purpose of the article is to examine the impact of long-term factors affecting human development in emerging market countries, based on the “middle income trap” hypothesis. According to the research question, the radical liberal reforms implemented in the countries of the former Soviet Union, including the Republic of Armenia, in the 1990s have led to the emergence of a middle income trap, which requires large expenditures and new reforms in human capital development to overcome. As a basic methodological approach, the problem of the relationship between human development and the middle income trap has been studied in the context of the dynamics of income differentiation and inequality indicators. According to the results of the study, in the Republic of Armenia, along with the economic growth recorded as a result of liberal reforms and the increase in the human development index, there has been an increase in the level of inequality, while the main factors restraining the latter are the progressive growth of public spending in the education and healthcare sectors. Among the factors that have a decisive impact on long-term human development, the spread of digital technologies, investments in research and development programs, as well as the neutralization of the effects of negative institutional factors, in particular, the reduction of corruption, are of decisive importance. The main findings of the study demonstrate that in the long run, overcoming the “middle income trap” is conditioned not only by increasing costs for education and healthcare sectors and gradual steps towards improving living standards, but also by programs of significant investments in improving the institutional environment.